Solutions for Unexpected Challenges Encountered when Integrating Research Genomics Results into the EHR - Rasmussen, Luke V.; Hoell, Christin; Smith, Maureen E.; Chisholm, Rex; Starren, Justin; Aufox, Sharon; Luo, Yuan; Rasmussen-Torvik, Laura J. (ACI Open, 2020)
Background While there have been published reports detailing technical challenges of incorporating genetic test results into the electronic health record (EHR) with proposed solutions, less has been published about unanticipated sociotechnological or practical communication challenges involved in this process.Objectives This study was aimed to describe unanticipated issues that arose returning genetic research results through the EHR as part of the National Human Genome Research Institute (NHGRI)-funded electronic Medical Records and Genomics (eMERGE) 3 consortium, and provide lessons learned for future implementationsMethods We sequenced 3,000 participants on a 109-gene panel and returned genetic results initially in person and/or by letter, with a later release directly into the EHR and patient portal.Results When results were returned through the EHR, multiple participants expressed confusion and contacted the health system, resulting in our institution temporarily freezing our return of research results.Discussion We determined the likely causes of this issue to be (1) the delay between enrollment and results return, (2) inability to personalize mass e-mail messages announcing new research test results in the EHR, (3) limited space for description of test results in the EHR, and (4) the requirement to list an ordering physician for research results in the EHR. For future return of results, we propose sending preparatory e-mails to participants, including screenshots of how they can expect to see their results presented in the EHR portal.Conclusion We hope our lessons learned can provide helpful guidance to other sites implementing research genetic results into the EHR and can encourage EHR developers to incorporate greater flexibility in the future.
Keywords: electronic health record; genetics; precision medicine